Endoscopic treatment of meningoencephaloceles of the anterior skull base - Rosa, João (2024)
Objectives: to review the casuistry of anterior skull base meningoencephaloceles and evaluate the effectiveness of endoscopic endonasal surgical treatment. Study Design: retrospective descriptive study. Materials and Methods: review of clinical and surgical records of patients undergoing endoscopic meningoencephalocele repair in a tertiary hospital center between 2017 and 2023. Results: thirteen patients were included, totaling 14 meningoencephaloceles. Etiologies encompassed benign intracranial hypertension (n=6), traumatic (n=5), idiopathic (n=2), and tumoural (n=1). The cribriform plate of the ethmoid (n=6) and the sphenoid sinus (n=6) were the most frequent locations. The surgical success rate was 100% (n=14). No major complications were observed. Conclusion: endoscopic endonasal correction of meningoencephaloceles demonstrated high efficacy and low morbidity, supporting existing literature.